School culture and teacher participation in P5 implementation in senior high schools - Ningsih, Setya; Setiawati, Merika; Rusdinal, Rusdinal; M, Sufyarma (Universitas Jambi, Indonesia, 2026)
This study examines how school culture and teacher participation contribute to the implementation of the Pancasila Student Profile Strengthening Project (P5) in Sekolah Penggerak senior high schools in Dharmasraya District. The challenges in P5 practice, such as limited teacher understanding, difficulties in preparing project modules, and weak coordination among teachers, motivated this study. A quantitative survey design was used, involving 66 teachers selected from a population of 165 teachers. Data were collected via a Likert-scale questionnaire and analyzed using correlation and multiple regression analyses. The findings indicate that school culture accounted for 24.5% of the variance in P5 implementation, while teacher participation contributed 59.7%. Together, the two variables explained 62.2% of the variance in P5 implementation. These results suggest that effective P5 practice requires a supportive school environment and active teacher involvement in planning, organizing, implementing, and evaluating project-based learning.